Network Simulation and Performance Evaluation of WiMAX Extensions for Isolated Research Data Networks - Bohnert, Thomas Michael (2008)
IEEE 802.16 is yet a very recent technology and released hardware does frequently only support standards partially. The same applies to public available simulation tools, in particular for NS-2. As the latter is the de-facto standard in science and as we use it for our research in the context of the WEIRD project, we evaluate the IEEE 802.16 support for NS-2. We present several general but also specific issues, which are important in order to carry out reliable research based on these tools. In particular, we show in much detail where modules deviate significantly and even fail totally.